Comparative Analysis of Cross Sectional and Time Series Momentum Strategies: An Empirical Study in UK and US Equity Markets - Mistry, Prachi Jaswant (2016)
The study compares the profitability of the cross sectional and time series momentum strategies across two developed markets, UK and US equity markets. We find that the cross sectional momentum strategy is not successful in the US market while the time series momentum strategy generate significant profitability in both the markets. However, the cross sectional momentum returns are found to be superior that that of the time series momentum strategy. These momentum returns are not a compensation for risk but an outcome of the behaviour of investors. An important findings of this paper is that the time series momentum strategy exhibit the ability to sustain positive returns during the “Down Markets” while the crashes magnifies the cross sectional momentum losses.